(untitled) (Bangladesh Journal of Child Health, 2017)
Respiratory failure secondary to surfactant deficiency is a major cause of morbidity and mortality in low birth weight premature infants. Surfactant therapy substantially reduces mortality and respiratory morbidity for this population. Exogenous surfactant therapy has become well established in newborn infants with respiratory distress. Many aspects of its use have been well evaluated in high-quality trials and systematic reviews. Secondary surfactant deficiency also contributes to acute respiratory morbidity in late-preterm and term neonates with meconium aspiration syndrome, pneumonia/ sepsis, and perhaps pulmonary hemorrhage; surfactant replacement may be beneficial for these infants. This article summarizes the evidence and gives recommendations for the use of surfactant therapy for respiratory distress syndrome (RDS) in newborn. Bangladesh J Child Health 2016; VOL 40 (1) :26-30